2004
DOI: 10.1038/oby.2004.111
|View full text |Cite
|
Sign up to set email alerts
|

Physical Frailty and Body Composition in Obese Elderly Men and Women

Abstract: VILLAREAL, DENNIS T., MARIAN BANKS, CATHERINE SIENER, DAVID R. SINACORE, AND SAMUEL KLEIN. Physical frailty and body composition in obese elderly men and women. Obes Res. 2004;12:913-920. Objective: To evaluate the prevalence of frailty and interrelationships among body composition, physical function, and quality of life in community-dwelling obese elderly (OE) persons. Research Methods and Procedures: Fifty-two OE, 52 nonobese frail, and 52 nonobese nonfrail subjects, matched for age and sex, were studied. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
294
6
12

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 396 publications
(325 citation statements)
references
References 44 publications
13
294
6
12
Order By: Relevance
“…On the other hand, the results of our study line up with those obtained by other researches (De Hollander et al, 2013;Pan, Cole, & Geliebter, 2011;Villareal, Banks, Siener, Sinacore, & Klein, 2004), showing that obesity worsens quality of life, particularly its physical dimension. However, it would be necessary to analyze if body composition modifications imply improvement in the perceived level of quality of life.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, the results of our study line up with those obtained by other researches (De Hollander et al, 2013;Pan, Cole, & Geliebter, 2011;Villareal, Banks, Siener, Sinacore, & Klein, 2004), showing that obesity worsens quality of life, particularly its physical dimension. However, it would be necessary to analyze if body composition modifications imply improvement in the perceived level of quality of life.…”
Section: Discussionsupporting
confidence: 92%
“…Em apenas três estudos os critérios de representatividade da amostra não foram identificados e a forma de seleção das pessoas do estudo foi por conveniência (13)(14)(15) Todos os estudos descritos na revisão abordavam a população na faixa etária igual ou acima de 65 anos, com exceção de dois estudos no qual abordavam a faixa etária de 43 a 86 anos (5) e acima de 50 anos (12), que foram incluídos na revisão por discriminar os resultados por faixa etária, sendo assim, utilizou-se apenas os resultados da amostra com 65 anos ou mais.…”
Section: Resultsunclassified
“…A higher proportion of connective tissue alters the quality of FFM, which can lead to functional disability and mobility limitations. 36 We excluded subjects aged 440 years, because Kyle et al 26 demonstrated that age-related differences in body cell mass and total body potassium were greater than the differences in FFM or appendicular lean soft tissue suggesting an altered composition of FFM with lower SM in older subjects.…”
Section: Discussionmentioning
confidence: 99%